Measuring Employee Happiness in the UAE – Integrating Organisational Data into the National Statistics - Benuyenah, Vic; Pandya, Bharti (International Review of Management and Marketing, 2020)
Measuring happiness is a complicated process as the concept of happiness cannot be universally defined, collectively experienced or scientifically measured. Further, the lag between when happiness is experienced and when a happiness research report is produced makes intervention efforts ineffective and occasionally redundant. In the current literature, confusions exist in terms of definitions of happiness, well-being and whether Gross Domestic Product (GDP) is an accurate measure of a nation's development. Within the organisational context however, little research is carried out on happiness leading whilst at the practical level, some nations including the United Arab Emirates and Bhutan, are currently promoting several happiness initiatives in order to become a happier nation and, perhaps, influence the country's productivity. We have proposed a simple data collection approach at the organisational level that will collect daily happiness data per each employee. The micro data collection process is different from the big data normally gathered by the state departments in the sense that it is timely, captures the individualized account of happiness which, we recommend, should be correlated with organisational productivity and fed into the overall national statistics on Gross National Product (GNP) and public well-being. Keywords: Organisational Happiness; Happiness Index; Gross National Happiness; UAE Happiness; Productivity and Happiness. JEL Classifications: J24, E71, N35 DOI: https://doi.org/10.32479/irmm.9698